Living in Complex Economies: On Inconsistent Expectations and Economic Crises - Heymann, Carlos Daniel (2013)
Economic crises are associated with large shocks to beliefs and expectations. Thus, their study includes the strategies that economic actors use to interpret and anticipate the evolution of their environment. In this setting, we start with a brief review of argu- ments on the possibilities and limitations of probabilistic approaches in economic contexts. Then, we discuss some accounts of the recent macroeconomic crisis, focusing on the problems which arise in predicting the dynamics of non- ergodic systems. Further, we concentrate on the various ways in which agents rationalize an economic path that will eventually be perceived as an unsustainable bubble. We conclude by stressing the relevance of paying attention to the concrete practices of actors in forming representations of the economy and determining expectations.